Um estudo sobre a implementaçã odo programa etnomatemática no contexto escolar - Pereira, Anderson Luis [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This research aims to present the Ethnomathematics Program, created by D'Ambrosio (1984), as a proposal for the teaching of mathematics, making it contextualized, meaningful and a program able to form critical and creative citizens, capable of transform reality. By presenting from Ethnomathematics perspective the conception of the activities, scholar curriculum and current evaluation system, a possibility of innovation on nowadays education system is opened, a system that is characterized by D'Ambrosio as obsolete. For the implementation of this proposal, a change on the teacher's attitude appears as necessary, a new attitude that makes active interferences during the learning process, and uses previous knowledge acquired by the student throughout their experiences as a starting point on teaching process. The approach between Ethnomathematics perspective and Mathematics Program provides a better opportunity for the students to construct mathematical knowledge. It is important to emphasize that the Ethnomathematics is as an interdisciplinary as a transdisciplinary program, which means that the Program is not restricted just for education and development of mathematics

Esta pesquisa tem por finalidade apresentar o Programa Etnomatemática criado por D’Ambrosio (1984), como uma proposta para o ensino da Matemática, tornando-a contextualizada, significativa e formadora de cidadãos críticos, criativos e transformadores de sua realidade. Por meio da apresentação da concepção de atividade, currículo e avaliação, na perspectiva da Etnomatemática, abre-se a possibilidade de inovar o sistema educacional caracterizado por D’Ambrosio como obsoleto. Para a implementação dessa proposta faz-se necessária, também, uma mudança de postura do professor de forma que interfira ativamente nesse processo de aprendizagem, utilizando o conhecimento adquirido pelo aluno, ao longo de suas vivências, como ponto de partida para o ensino. A aproximação entre o Programa Etnomatemática e a Matemática dá ao aluno a oportunidade de construir o conhecimento matemático. É importante destacar que o Programa Etnomatemática é interdisciplinar e transdisciplinar, ou seja, não é voltado apenas para a educação e desenvolvimento da Matemática
Keywords: Matemática - Estudo e ensino; Etnomatematica; Sistemas de ensino - Projetos; Mathematics Study and teaching